2023
DOI: 10.3390/nu15071660
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of 11-Keto-β-Boswellic Acid against Diabetic Cardiomyopathy in Rats Entails Activation of AMPK

Abstract: This study examined the protective effect of 11-keto-β-boswellic acid (AKBA) against streptozotocin (STZ)-induced diabetic cardiomyopathy (DC) in rats and examined the possible mechanisms of action. Male rats were divided into 5 groups (n = 8/each): (1) control, AKBA (10 mg/kg, orally), STZ (65 mg/kg, i.p.), STZ + AKBA (10 mg/kg, orally), and STZ + AKBA + compound C (CC/an AMPK inhibitor, 0.2 mg/kg, i.p.). AKBA improved the structure and the systolic and diastolic functions of the left ventricles (LVs) of STZ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 103 publications
0
1
0
Order By: Relevance
“…In addition, the data of this study also confirmed inflammation in the LVs of these rats by the significant upregulation in the mRNA levels and nuclear levels of NF-κB and higher levels of ICAM-1, TNF-α, IL-6, and IL-1β. These data follow many other studies that have also shown similar results on the reduction in these antioxidant levels and in the elevation of MDA, TNF-α, IL-6, and collagen levels, as well as the of NF-κB in the hearts of STZ-diabetic rats [32,[50][51][52][53][54][55][56][57]. However, restoring all of these biochemical endpoints in the LVs of these rats was our strongest evidence that the cardioprotective effect of ESA is mediated by suppressing oxidative stress, inflammation, and fibrosis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the data of this study also confirmed inflammation in the LVs of these rats by the significant upregulation in the mRNA levels and nuclear levels of NF-κB and higher levels of ICAM-1, TNF-α, IL-6, and IL-1β. These data follow many other studies that have also shown similar results on the reduction in these antioxidant levels and in the elevation of MDA, TNF-α, IL-6, and collagen levels, as well as the of NF-κB in the hearts of STZ-diabetic rats [32,[50][51][52][53][54][55][56][57]. However, restoring all of these biochemical endpoints in the LVs of these rats was our strongest evidence that the cardioprotective effect of ESA is mediated by suppressing oxidative stress, inflammation, and fibrosis.…”
Section: Discussionsupporting
confidence: 91%
“…Also, intrinsic cell apoptosis is characterized by the reduced expression of anti-apoptotic genes (e.g., Bcl2), the overexpression of apoptotic genes such as Bax, damaged mitochondria, and increased mitochondrial cytochrome-c release, which ultimately activates caspase-3 and caspase-9, fragmenting the DNA [62]. Both extrinsic and intrinsic cell death modality was observed in the diabetic hearts of STZ-treated animals, as well as in the LV biopsies of patients with T1DM, and was attributed to oxidative damage [55,57,58,63]. Intrinsic cell apoptosis was also confirmed in the LVs of the STZ-diabetic animals in this study, as shown by their high cytoplasmic content of cytochrome-c, Bax, and caspase-3 and the lower levels of Bcl2.…”
Section: Discussionmentioning
confidence: 99%
“…AKBA is an active compound extracted from B. serrata with anti-inflammatory and antioxidant activity; however, its bioavailability is low due to its instability and poor solubility in water . The utilization can be improved by embedding it in an amphiphilic substance.…”
Section: Resultsmentioning
confidence: 99%
“…Нарушение передачи сигналов кальция в митохондриях обусловливает недостаток или избыток концентрации кальция в саркоплазме и нарушение сокращения кардиомиоцитов. Повышенный окислительный стресс также является признаком митохондриальной дисфункции, и мутации в генах, участвующих в механизмах антиоксидантной защиты, могут усугублять окислительное повреждение и способствовать развитию ГКМП [62,63]. В этот процесс могут быть вовлечены гены, кодирующие антиоксидантные ферменты супероксиддисмутазу или глутатионпероксидазу [64].…”
Section: морфофункциональные нарушения митохондрий при гипертрофическ...unclassified